Analisis Kelayakan Unit Usaha Perahu Motor Tempel Dengan Alat Tangkap Gillnet di Perairan Lampu Satu Merauke, Papua - Baso Mappasessu; Marius Agustinus Welliken (Faculty of Agriculture Musamus University, 2021)
Gillnet is one of the fishing gear used by fishermen in Coast Lampu Satu, Merauke, the outboard motor business unit with gillnet fishing gear uses ± 40-60 pieces so it requires very large business capital. The purpose of this study was to determine the feasibility of an outboard motor boat business unit with gillnet fishing gear. The data collection technique was carried out by collecting data through field observations and interviews. Methods of data analysis with technical analysis and financial analysis. The results showed that the B / C Ratio value was 1.07, the NPV value was Rp. 52.526.857, the IRR value is 15,92% and PP is 2.8 years, indicating that the outboard motor business unit with fishing gillnet fishing.